Download presentation

Presentation is loading. Please wait.

Published byRudolf Jones Modified over 8 years ago

2
EXAMPLE 1 Factor ax 2 + bx + c where c > 0 Factor 5x 2 – 17x + 6. SOLUTION You want 5x 2 – 17x + 6 = (kx + m)(lx + n) where k and l are factors of 5 and m and n are factors of 6. You can assume that k and l are positive and k ≥ l. Because mn > 0, m and n have the same sign. So, m and n must both be negative because the coefficient of x, –17, is negative.

3
EXAMPLE 1 Factor ax 2 + bx + c where c > 0 ANSWER The correct factorization is 5x 2 –17x + 6 = (5x – 2)(x – 3).

4
EXAMPLE 2 Factor ax 2 + bx + c where c < 0 Factor 3x 2 + 20x – 7. SOLUTION You want 3x 2 + 20x – 7 = (kx + m)(lx + n) where k and l are factors of 3 and m and n are factors of –7. Because mn < 0, m and n have opposite signs. ANSWER The correct factorization is 3x 2 + 20x – 7 = (3x – 1)(x + 7).

5
GUIDED PRACTICE for Examples 1 and 2 GUIDED PRACTICE Factor the expression. If the expression cannot be factored, say so. 1. 7x 2 – 20x – 3 (7x + 1)(x – 3) 2. 5z 2 + 16z + 3 3. 2w 2 + w + 3 cannot be factored ANSWER (5z + 1)(z + 3). ANSWER

6
GUIDED PRACTICE for Examples 1 and 2 GUIDED PRACTICE 5. 4u 2 + 12u + 5 (2u + 1)(2u + 5) 6. 4x 2 – 9x + 2 (4x – 1)(x – 2) 4. 3x 2 + 5x – 12 (3x – 4)(x + 3) ANSWER

7
EXAMPLE 3 Factor with special patterns Factor the expression. a. 9x 2 – 64 = (3x + 8)(3x – 8) Difference of two squares b. 4y 2 + 20y + 25 = (2y + 5) 2 Perfect square trinomial c. 36w 2 – 12w + 1 = (6w – 1) 2 Perfect square trinomial = (3x) 2 – 8 2 = (2y) 2 + 2(2y)(5) + 5 2 = (6w) 2 – 2(6w)(1) + (1) 2

8
GUIDED PRACTICE for Example 3 Factor the expression. 7. 16x 2 – 1 (4x + 1)(4x – 1) 8. 9y 2 + 12y + 4 (3y + 2) 2 9. 4r 2 – 28r + 49 (2r – 7) 2 10. 25s 2 – 80s + 64 (5s – 8) 2 ANSWER

9
GUIDED PRACTICE for Example 3 11. 49z 2 + 4z + 9 (7z + 3) 2 12. 36n 2 – 9 = (3y) 2 (6n – 3)(6n +3) ANSWER

10
EXAMPLE 4 Factor out monomials first Factor the expression. a. 5x 2 – 45 = 5(x + 3)(x – 3) b. 6q 2 – 14q + 8 = 2(3q – 4)(q – 1) c. –5z 2 + 20z d. 12p 2 – 21p + 3 = 5(x 2 – 9) = 2(3q 2 – 7q + 4) = –5z(z – 4) = 3(4p 2 – 7p + 1)

11
GUIDED PRACTICE for Example 4 Factor the expression. 13. 3s 2 – 24 14. 8t 2 + 38t – 10 2(4t – 1) (t + 5) 3(s 2 – 8) 15. 6x 2 + 24x + 15 3(2x 2 + 8x + 5) 16. 12x 2 – 28x – 24 4(3x + 2)(x – 3) 17. –16n 2 + 12n –4n(4n – 3) ANSWER

12
GUIDED PRACTICE for Example 4 18. 6z 2 + 33z + 36 3(2z + 3)(z + 4) ANSWER

13
EXAMPLE 5 Solve quadratic equations Solve (a) 3x 2 + 10x – 8 = 0 and (b) 5p 2 – 16p + 15 = 4p – 5. a. 3x 2 + 10x – 8 = 0 (3x – 2)(x + 4) = 0 3x – 2 = 0 or x + 4 = 0 Write original equation. Factor. Zero product property Solve for x. or x = –4 x = 2323

14
EXAMPLE 5 Solve quadratic equations b. 5p 2 – 16p + 15 = 4p – 5. Write original equation. 5p 2 – 20p + 20 = 0 p 2 – 4p + 4 = 0 (p – 2) 2 = 0 p – 2 = 0 p = 2 Write in standard form. Divide each side by 5. Factor. Zero product property Solve for p.

15
GUIDED PRACTICE for Examples 5, 6 and 7 Solve the equation. 19. 6x 2 – 3x – 63 = 0 or –3 3 1212 20. 12x 2 + 7x + 2 = x +8 no solution 21. 7x 2 + 70x + 175 = 0 –5 ANSWER

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google